Structure of the heme o prosthetic group from the terminal quinol oxidase of escherichia coli - Wu, Wei; Chang, Chi; Varotsis, Constantinos (My University, 1992)
The structure of the heme o prosthetic group of Escherichia coli quinol oxidase (cytochrome o oxidase) has been unambiguously determined by preparation and characterization of its iron-free derivative porphyrin o dimethyl ester, or dimethyl 2,7,12,18-tetramethyl-3-[(4E,8E)-1-hydroxy-5,9,13-trimethyltetradeca-4,8,12- trienyl]-8-vinylporphine-13,17-dipropionate. The identity of this natural porphyrin dimethyl ester was established by 1H NMR, MS, IR, and RR spectroscopies as well as by comparisons with model compounds and the closely related porphyrin a dimethyl ester. The reliability of the structure determination was further strengthened by the isolation and characterization of the acetylated and dehydrated derivatives of porphyrin o
Keywords: Heme; Escherichia coli; Cytochrome oxidase; Porphyrins; Oxygen; Enzymes